Evaluation and Mitigation of Electromagnetic Interference Between Railways and Nearby Power Lines: A Review - Chenyang Wang (IEEE, 2021)
A railway running near power lines is subjected to electromagnetic interference from power lines, which can adversely affect normal operation of the railway’s communication and signaling system, resulting in safety hazard on the railway equipment and personnel. Therefore, it is very important to assess such electromagnetic interference issues to ensure the railway system’s reliability and the public safety. In this paper, a literature review is conducted on electromagnetic interference between railways and nearby power lines, which has not been widely researched in the past. Although IEEE Standard 2746–2020 has raised the importance of such electromagnetic interference, but it only offers very basic information without an in-depth coverage. This paper provides a review, where critical aspects of electromagnetic interference between railways and power lines are summarized and the future research direction in this area is recommended.